Roots, radicals and rockers : how skiffle changed the world - Bragg, Billy (Faber & Faber, 2017)
"Emerging from the jazz clubs of the early 1950s, skiffle -- a uniquely British take on American folk and blues -- caused a sensation among a generation of kids who had grown up during the dreary post-war years. These were Britain's first teenagers, looking for a music of their own in a culture dominated by crooners and mediated by a stuffy BBC. Sales of guitars rocketed from 5,000 to 250,000 a year, and -- as with the punk rock that would flourish two decades later -- all you needed to know were three guitar chords to form your own group, with your mates accompanying on tea-chest bass and washboard. Against a backdrop of Cold War politics, rock and roll riots and a newly assertive working-class youth, Billy Bragg charts -- for the first time in depth -- the history, impact and legacy of Britain's original pop movement. It's a story of jazz pilgrims and blues blowers, Teddy Boys and beatnik girls, coffee-bar bohemians and refugees from the McCarthyite witch-hunts, who between them sparked a revolution that shaped pop culture as we have come to know it"--Page 2 of dust jacket.